2002
DOI: 10.1021/om0203227
|View full text |Cite
|
Sign up to set email alerts
|

Neutral and Anionic Silyl Hydride Derivatives of the Tantalum Imido Fragment Cp*(DippN)Ta (Cp* = η5-C5Me5; Dipp = 2,6-iPr2C6H3). Reactive σ-Bonds and Intramolecular C−H Bond Activations Involving the Silyl Ligands

Abstract: The syntheses and reactivities of alkyl, silyl, and hydride complexes of the type Cp*(DippN)TaRR‘ (Cp* = η5-C5Me5; Dipp = 2,6-iPr2C6H3; R = silyl, alkyl; R‘ = alkyl, hydride) are described. The compounds Cp*(DippN)Ta(SiR3)Cl (SiR3 = Si(SiMe3)3 (1), SiPh3 (2), SiHMes2 (3); Mes = 2,4,6-Me3C6H2), prepared from Cp*(DippN)TaCl2 and (THF) n LiSiR3, react with H2 to yield the dimeric hydride [Cp*(DippN)TaCl(μ-H)]2 (4). The reaction of 4 with (THF)3LiSi(SiMe3)3 (2 equiv) gave the 16-electron silyl hydride complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 65 publications
5
52
0
1
Order By: Relevance
“…15 it was reported that this is also the region where the hydride signal of terminal Nb-H 16 and Ta-H 17 bonds are observed for this type of dicyclopentadienyl imido complexes. The difference between the 13 C quaternary and methyl carbon resonances of the tertbutylimido group is 30.8 ppm suggesting a linear disposition of the Nb-N-tBu ligand in complex 15.…”
Section: Methodsmentioning
confidence: 64%
“…15 it was reported that this is also the region where the hydride signal of terminal Nb-H 16 and Ta-H 17 bonds are observed for this type of dicyclopentadienyl imido complexes. The difference between the 13 C quaternary and methyl carbon resonances of the tertbutylimido group is 30.8 ppm suggesting a linear disposition of the Nb-N-tBu ligand in complex 15.…”
Section: Methodsmentioning
confidence: 64%
“…[1] For example, Cp/imido, bisA C H T U N G T R E N N U N G (imido) and alkoxyimido ligand sets have been widely used for the preparation of metallocene-like catalysts for olefin polymerization, [2] dehydrogenative polymerization of silanes [3] and olefin metathesis. [4] In addition to its role as a supporting ligand for reactive groups elsewhere in a metals coordination sphere, such as silyl and hydride ligands, [3,5] the unsaturated and polar M=NR bond itself can act as a potent reaction site towards addition reactions with saturated and unsaturated substrates.…”
Section: Introductionmentioning
confidence: 99%
“…[1] For example, Cp/imido, bisA C H T U N G T R E N N U N G (imido) and alkoxyimido ligand sets have been widely used for the preparation of metallocene-like catalysts for olefin polymerization, [2] dehydrogenative polymerization of silanes [3] and olefin metathesis. [4] In addition to its role as a supporting ligand for reactive groups elsewhere in a metals coordination sphere, such as silyl and hydride ligands, [3,5] the unsaturated and polar M=NR bond itself can act as a potent reaction site towards addition reactions with saturated and unsaturated substrates. [6] 3 ) 2 ] (M= V, Nb) with silanes afford a plethora of products, depending on the nature of the metal, substitution at silicon and 3 ) 2 ] bearing a penta-coordinate silicon centre, which then rearranges into the final products through a SiÀH or SiÀCl bond activation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…101 Silyl derivatives of group 5 organometallic complexes have been investigated including intramolecular C-H activation of silyl ligands by tantalum() imido moieties 102 and the formation of an unusual imido-bridged 1,3-disilaniocyclobutane 11 from reaction between [Nb(η 5 -C 5 H 5 )(H)(SiMe 2 I) 2 ] and H 2 NEt 2 . 103 Hydrogenation of aromatics 104 and intramolecular hydride transfers to aromatic rings have been studied and an investigation into dihydrogen addition to [Ta(CH 2 )-(η 5 -C 5 Me 5 ) 2 (H)] using parahydrogen has also been reported.…”
Section: Vanadium Niobium Tantalummentioning
confidence: 99%